Faktor-Faktor yang Mempengaruhi Pengembangan Kriket sebagai Olahraga Minor di Indonesia: Systematic Literature Review - Novita Sari; Mela Suhariyanti (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The slow development of kriket as a minor sport in Indonesia remains a problem, primarily due to a lack of support across various areas such as policy, facilities, and low public participation. Limited exposure and public awareness mean that this sport is not yet widely known compared to other sports. Therefore, a comprehensive study is required to identify the factors influencing the development of kriket in Indonesia. The aim of this study is to analyse the various factors that influence the development of kriket as a minor sport in Indonesia. The method used is a Systematic Literature Review (SLR) guided by PRISMA. Data was obtained from Google Scholar covering the years 2021–2025 using the keywords “kriket development”, “development of kriket”, “minor sport”, and “sports development factors”, resulting in 10 articles which were analysed using content analysis techniques. The findings indicate that the development of kriket is influenced by several key factors, namely government support, the role of sports organisations, the availability of facilities and infrastructure, athlete development systems, and public participation and interest. It is concluded that the development of kriket requires synergy among various parties and integrated strategies to ensure optimal development. Consequently, more intensive efforts are required in coaching, promotion, and the provision of facilities, with the recommendation that.